La consciencia : ¿una realidad no algorítmica? (2007)
ABSTRACT: Conscience is again at the center of attention of psychologists and scientists in general, and it has not stopped being that way for many philosophers. Nevertheless, there’s no agreement about the way in which conscience can be understood. Two extreme positions can be highlighted: One of them considers that its essential stamp is non-algorithmic, and therefore, in its performance there are elements that can’t be predicted. The other one states that conscience is a superior human capacity associated with language and rational activity. Between these two opposite interpretations there are different considerations about the nature of language and the aspects that take part in the human capacity to create and invent. This paper analyzes these positions, their confl uences and contradictions, and proposes a conceptual integration that tries to solve the divergences presented, especially those that are related to the infl uence of language, intuition, chance and reason in the performance of the conscience.